Personality descriptions influence perceived cuteness of children and nurturing motivation toward them. - Reina Takamatsu; Takashi Kusumi; Hiroshi Nittono (PLoS ONE, 2023)
The current empirical evidence regarding the effects of personality on physical attractiveness is limited to adult faces. In two preregistered studies, we demonstrated that personality descriptions influenced perceived cuteness, warmth, competence of young children, and female adults' nurturing motivation toward them. Study 1 showed that participants rated children accompanied by positive personality descriptions as cuter, friendlier, and more intelligent than their initial ratings. Negative personality descriptions reduced perceived cuteness in children, which in turn reduced nurturing motivation. Study 2 showed that negative personality descriptions consistently reduced perceived cuteness and warmth ratings after manipulation, regardless of the initial level of perceived cuteness. After one week, cuteness and warmth ratings in the positive personality condition tended to return to their initial ratings. However, the effect of negative personality descriptions on cuteness ratings persisted for all children. Together, our findings suggest that female adults' perception of cuteness and nurturing motivation are induced not only by children's appearance but also their personality.